Structural region essential for amyloid fibril formation in cytochrome c elucidated by optical trapping. Issue 92 (31st October 2022) - Hirota, Shun; Chiu, Chun-Liang; Chang, Chieh-Ju; Lo, Pei-Hua; Chen, Tien; Yang, Hongxu; Yamanaka, Masaru; Mashima, Tsuyoshi; Xie, Cheng; Masuhara, Hiroshi; Sugiyama, Teruki
Abstract : Amyloid fibril formation of cytochrome c is spatially and temporally controlled by the optical trapping method, identifying that the structural change in the region containing Ala83 is essential for the amyloid fibril formation. Abstract : Amyloid fibril formation of cytochrome c is spatially and temporally controlled with a combined method of disulfide bond cross-linking of cysteine-introduced variants and optical trapping, identifying that the structural change in the region containing Ala83 is essential for the amyloid fibril formation.